Animal welfare index: an animal welfare evaluation of beef production farms in Ireland. Issue 1 (31st December 2022) - Lawrence, Peter; McGee, Mark; Earley, Bernadette
ABSTRACT: The study objective was to examine the animal welfare status of Irish beef production farms using an animal welfare index (AWI). Beef production farms ( n = 105) including suckler calf-to-beef ( n = 30), suckler calf/weaning/finishing ( n = 63), dairy calf-to-beef ( n = 12) were assessed during the winter housing period using the AWI. Fifty-one indicators were grouped into six categories: 'locomotion'; six indicators, 'social interactions'; eight indicators, 'flooring'; four indicators, 'environment'; nine indicators, 'stockperson'; thirteen indicators and 'husbandry management' seven indicators. Two indicators relating to the size of the farm and number of animals on the farm were also collected. The overall mean AWI percentage for the suckler calf-to-beef, suckler calf/weaning/finishing, dairy calf-to-beef farms were 70.3%, 71.9% and 66.6%, respectively. There was no difference ( P > 0.05) in AWI between full-time and part-time farmers. This study demonstrated the application of the AWI for use in beef production systems.